Kolaborasi Multi Aktor dalam Program Restorasi Gambut di Provinsi Riau - Wicaksono, Agung (Jurnal Administrasi dan Kebijakan Publik, 2019)
Peat restoration as a government strategic program is a hot issue. This was initially thought to be the result of forest and peat fires which were the source of the worst smoke disasters in 2015. The World Bank estimated the impact of economic losses at Rp. 221 Trilliuns. In accordance with Perpres No. 1 In 2016, the government established the Peat Restoration Agency which became the leader in the implementation of peat restoration in Indonesia. It is important to note that peat restoration was designed with the framework of collaboration with many actors. Governments, communities, NGOs and the private sector are key actors in implementing peat restoration (collaborative governance). The actor's approach is the focus of this research by using collaborative governance theory as the main framework of research. This research uses a qualitative method with a case study approach. Researchers found that there was a failure of collaboration between actors in the peat restoration program in Riau. The unclear status of the Regional Peat Restoration Team (TRGD) and the inactivity of the Riau Provincial Government in supporting the peat restoration agenda are the findings of this study. Researchers see there are several factors that cause it to happen. Economic factors are the main because peat restoration is related to investment in forestry and oil palm plantations. Then the cause of the failure of collaboration between these actors was also caused by the lack of commitment from political leaders in Riau.